2008
DOI: 10.1111/j.1398-9995.2008.01635.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and immunological characterization of novel weed pollen pan‐allergens

Abstract: The identified proteins are novel pan-allergens and can be used as diagnostic markers for polysensitization and used in component-resolved diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 28 publications
2
43
0
Order By: Relevance
“…Amb a 8 has been found to have an 89% amino acid sequence identity with Art v 4 (4). In addition to their sequence identity, both Art v 4 and Amb a 8 have comparable IgE cross-reactivity, suggesting that either allergen could be used as a marker for profilin sensitization in weeds (4). Moreover, we compared molecular and immunological properties of Amb a 8 and Art v 4 with those of Bet v 2, a birch pollen profilin.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Amb a 8 has been found to have an 89% amino acid sequence identity with Art v 4 (4). In addition to their sequence identity, both Art v 4 and Amb a 8 have comparable IgE cross-reactivity, suggesting that either allergen could be used as a marker for profilin sensitization in weeds (4). Moreover, we compared molecular and immunological properties of Amb a 8 and Art v 4 with those of Bet v 2, a birch pollen profilin.…”
mentioning
confidence: 99%
“…Short ragweed, as well as giant ragweed, acts as a major elicitor of type 1 allergenic reactions in late summer and early fall, affecting over 15 million people in the United States and Canada (15). Amb a 8 has been found to have an 89% amino acid sequence identity with Art v 4 (4). In addition to their sequence identity, both Art v 4 and Amb a 8 have comparable IgE cross-reactivity, suggesting that either allergen could be used as a marker for profilin sensitization in weeds (4).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The clinical relevance of Unauthenticated Download Date | 5/8/18 8:27 AM polcalcin sensitization is linked to geographical factors and to the level of exposure to different allergenic sources. It has been shown that among weed pollenallergic patients, IgE reactivity to polcalcins from mugwort and ragweed, is much higher in Italians (21 to 28%) when compared to Austrians (10%) 29 . Monitoring of polcalcin-sensitized patients should be performed as these individuals are at risk of developing multiple pollen sensitizations 23 .…”
Section: Polcalcins and Allergic Rhinitismentioning
confidence: 99%